Doença peri-implantar: follow-up microbiológico de 5 anos e revisão sistemática com meta-análise - Sergio Diniz Ferreira (2016)
Aims: Evaluate, in a 5-year longitudinal study, the association between peri-implant diseases (DPi) diagnosis and the count of pathogens in the presence and absence of periodontal/peri-implant maintenance therapy. Conduct a systematic review of observational studies to evaluate whether data in the literature indicates a higher prevalence of peri-implantitis (PI) in subjects with diagnosis or history of periodontitis (PE). Methods: the microbiologic study was performed evaluating, through polymerase chain reaction in real time technique, the following bacterial species: T.forsythia, T. denticola, P. gingivalis, P. intermedia, F. nucleatum and A. naeslundii in 80 patients with peri-implant mucositis (PM) that were queries for periodontal/periimplant regular maintenance (GTP, n = 39) compared to those who were not (GNTP, n = 41). For the systematic review an electronic search was conducted until March 2016. It was found 1330 studies, 19 articles were included in the final analysis (PROSPERO CRD42015009518). The meta-analysis was performed for presence orabsence of PI. Summary measures and odds ratio (OR) with 95% IC were calculated. Results: the results of the longitudinal study showed that, after 5 years, there was a decrease in the total bacterial load (TBL), the frequency of bacteria analyzed in the orange complex (p = 0.013) and in the frequencies of T. forsythia (p = 0.000), P. gingivalis (p = 0.003) and P. intermedia (p = 0.013) in the GTP. Individuals with PI had higher frequencies of P. gingivalis (GNTP: p = 0.030; GTP: p = 0.000), T.denticola (GNTP: p = 0.017) and T. nucleatum (GTP and GNTP; p = 0.002) compared to those with PM diagnosis. Individuals who have developed PI showed an increase in TBL (GTP: p = 0047; GNTP: p = 0.055) and in the isolated frequencies of P. gingivalis (GNTP: p = 0.002) and F. nucleatum (GTP and GNTP; p = 0.000). There were no statistically significant differences intergroups in relation to red complex pathogens (p > 0.05). Both in individuals with PM (T1 and T2: p = 0.000), as in individuals with PI (T2: p = 0.000), the frequency of orange complex was significantly lower in the GTP. The meta-analysis of cohort studies showed that individuals (OR = 7.22), and implants (OR = 5.63) presented a higher risk of developing PI. In the cross-sectional studies, in unadjusted analyses, individuals with PE presented a higher chance of having PI (OR = 3.18). When the analysis was adjusted for smoking and diabetes, there was no statistically significant increase in risk for PI (OR = 1.73; 95% CI 0.86-3.45). Conclusions: it might be concluded that the absence of regular periodontal/peri-implant maintenance was associated with worse peri-implant clinical condition, higher incidence of PI and a significant increase in TBL. Additionally, individuals diagnosed with PI showed greater frequencies of P. gingivalis, T. denticola and F. nucleatum and largest TBL. The systematic review showed that individuals diagnosed or with PEs history may have an increased risk for PI. More prospective studies are needed to confirm this evidence, especially the randomized controlled clinical trials.